From Dickens’s Theatrical Performance to Contemporary post Dickensian Narrative and Artistic Performance (Acker, Ackroyd, Waters and Rushdie) - Georges Letissier (Cahiers Victoriens et Edouardiens)
Recent studies have underlined the relevance of the Victorian Age (whose temporal boundaries have been stretched to include the “long nineteenth century”) to the postmodern era. This essay narrows the topic to Dickens’s own relevance to postmodern aesthetics, through the question of theatricality. Dickens’s invention of public readings may be seen as an innovative method to advertise literary production, but it is also a tangible illustration of the type of boundary crossing valued by postmodern writers. With Dickens, who in this respect is very much in the Sternean-Shandian vein, theatrical performance is both inside the text (e.g. the parodic staging of Hamlet in Great Expectations) and outside the text, when dramatized versions of his novels are specially written to be acted out. It is the author’s versatility (implied as he was in a whole range of activities: fiction-writing, editing, journalism, publishing initiatives, amateur theatricals, speeches, public readings, business undertakings and so forth), together with the plurality within his works (the neo-baroque effect, perceptible among other things through the so-called “streaky bacon” or the “wonderful gargoyles”), which have served as a springboard for contemporary fiction-writers. Sarah Waters’s fictions, notably Fingersmith, have been almost unanimously praised for their plots, described as sheer “tour de force”. It can be claimed that Waters’s narrative ploys are borrowed from the theatrical world which held a real fascination for Dickens. With English Music, Ackroyd, for his part, illustrates what Clayton in his study: Charles Dickens in Cyberspace (2003) calls “undisciplined” creativity, by revisiting Great Expectations trans-artistically, through an odd combination of the pictorial, the musical, the cinematographic and the theatrical. This curious mixture of genres turns narration into fictionalized artistic performance, devised as a paean to the English tradition. At the other end of the spectrum, more iconoclastic literary experiments may be seen as bearing witness to Dickens’s off-the-beaten-track approach to novel-writing. Kathy Acker’s Great Expectations, by juxtaposing disjointed jump-cut sequences incorporating fantasy, personal statements and plagiarism transforms Dickensian theatrical performance into “narrative happenings”. As for Rushdie, the few pages he dedicates to Our Mutual Friend in his Satanic Verses capitalize on Dickens’s histrionic exuberance to stun the reader through verbal fireworks.